STRATEGIES FOR ECONOMIC DEVELOPMENT OF SMALL AND MEDIUM-SIZED ENTERPRISES IN MODERN CONDITIONS - С. О. Тульчинська; М. Є. Болтрик; Р. В. Тульчинський (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut")
The article studies the current aspects of the economic development strategy of small and medium-sized enterprises in modern conditions. The state of development of small and medium-sized enterprises in Ukraine is analyzed. It is established that flexibility and the ability to quickly adapt to changes in the external environment make small and medium-sized enterprises key participants in transformation processes in the modern economy. It is determined that to develop an economic development strategy regardless of the market and country, enterprises should use: PESTLE analysis, SWOT analysis, "Porter's Five Forces", etc. It is determined that among the state support instruments that can be included in the economic development strategy, the use of tax breaks, subsidies, grant programs, etc. can be considered. For the sustainability of small and medium-sized enterprises, it is worth considering work within clusters and cooperation, which allows reducing costs through the joint use of resources and increasing competitiveness. Effective implementation of strategies for the development of small and medium-sized enterprises will contribute to increasing the sustainability of the economy, its competitiveness and integration into global processes.